2020
DOI: 10.1186/s12884-020-03279-y
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal screening in the era of non-invasive prenatal testing: a Nationwide cross-sectional survey of obstetrician knowledge, attitudes and clinical practice

Abstract: Background Non-invasive prenatal testing (NIPT) has revolutionized the prenatal screening landscape with its high accuracy and low false positive rate for detecting Trisomy 21, 18 and 13. Good understanding of its benefits and limitations is crucial for obstetricians to provide effective counselling and make informed decisions about its use. This study aimed to evaluate obstetrician knowledge and attitudes regarding NIPT for screening for the common trisomies, explore how obstetricians integrated NIPT into fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Having discussed all the problems of NIPT, for individual settings and considering the ethical considerations under which each human genetic counsellor (MD or non-MD) is trained, it is really hard to understand that actual papers start with sentences like: “NIPT has revolutionized the approach to prenatal diagnosis and, to date, it is the most superior screening method for the common autosomal aneuploidies” [ 53 ]; or with: “our findings show the diversity of clinical practice with regard to the incorporation of NIPT into prenatal screening algorithms, and suggest that the use of NIPT both as a first-line screening tool in the general obstetric population, and to screen for SCAs and CNVs, is becoming increasingly prevalent” [ 54 ]. There is an urgent need to come back to the couple, patient and unborn child perspective and away from cost and profit argumentations.…”
Section: Discussionmentioning
confidence: 99%
“…Having discussed all the problems of NIPT, for individual settings and considering the ethical considerations under which each human genetic counsellor (MD or non-MD) is trained, it is really hard to understand that actual papers start with sentences like: “NIPT has revolutionized the approach to prenatal diagnosis and, to date, it is the most superior screening method for the common autosomal aneuploidies” [ 53 ]; or with: “our findings show the diversity of clinical practice with regard to the incorporation of NIPT into prenatal screening algorithms, and suggest that the use of NIPT both as a first-line screening tool in the general obstetric population, and to screen for SCAs and CNVs, is becoming increasingly prevalent” [ 54 ]. There is an urgent need to come back to the couple, patient and unborn child perspective and away from cost and profit argumentations.…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies have shown that clear guidance and continuing educational support are necessary for healthcare providers in this rapidly evolving area. [42][43][44][45][46]…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, for previous KAP surveys of NIPT, most of the respondents were obstetricians. 42,44,45,47 Considering that NIPT is primarily associated with prenatal diagnosis, our survey was completed by a wide range of HCPs working in prenatal diagnosis. This included HCPs of different specialties, years of practice, education levels, and hospital workplaces.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…This is following recommendations from the American College of Obstetricians and Gynaecologists in 2020 8 . NIPS is offered as a primary screening test option to all women in Singapore 9 . This is, however, self‐funded, in contrast to countries, such as Belgium where NIPS is publicly funded 10 .…”
Section: Introductionmentioning
confidence: 99%
“… 8 NIPS is offered as a primary screening test option to all women in Singapore. 9 This is, however, self‐funded, in contrast to countries, such as Belgium where NIPS is publicly funded. 10 Despite its relatively high‐cost ranging from Singapore Dollar (SGD) 1100 to SGD 2500, 11 the high sensitivity of NIPS at 99% as well as the non‐invasive nature of the test still makes it an attractive and acceptable option to pregnant women.…”
Section: Introductionmentioning
confidence: 99%